Three-phase Variable Speed Drive Using ARM Cortex-M3 - Muhamad Aiman, Muhamad Azmi; Hamdan, Daniyal; Mohd. Shafie, Bakar; Abu Zaharin, Ahmad (2014)
This paper focuses on the design and development of variable speed drive (VSD) for induction machine (IM) application. The estimation of frequency or speed produced in the voltage source inverter (VSI) will express the reliability and the efficiency of the system. The usage of renowned ARM Cortex-M3 processor embedded in Arduino DUE is selected as a controller for easy implementation and minimal computational power. The sinusoidal pulse width modulation (Sine-PWM) technique is used to drive the VSD with constant torque configuration to analyze the variation of speed towards the performance of the IM system. The experimental verification was conducted in open loop Volts per Hertz control (V/F)